Stereocontrolled Synthesis of Paracentrone - Nishioka, Yuto; Yano, You; Kinashi, Naoto; Oku, Natsumi; Toriyama, Yohei; Katsumura, Shigeo; Shinada, Tetsuro; Sakaguchi, Kazuhiko (Synlett, 2017)
The stereocontrolled total synthesis of the C31 apocarotenoid paracentrone was achieved by sequential cross-coupling reactions using C5 boronic acid ester and iodo-substituted dienes, which were newly developed building blocks for elongation of the conjugated polyene systems at both their terminals.
Keywords: apocarotenoid; paracentrone; fucoxanthin; cross-coupling; C5 diene; allene